HUBUNGAN TINGKAT PENGETAHUAN TENTANG HIV/AIDS DENGAN PEMANFAATAN LAYANAN CARE, SUPPORT, AND TREATMENT PADA X WANITA PEKERJA SEKSUAL - Hilman Mulyana (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2020)
Introduction: Tasikmalaya City is located in the province of West Java with HIV / AIDS cases ranked 13th, until 2020 it has reached 758 cases. In 2020 to May, there were 51 cases, mostly because their husbands like to “snack” and ironically this city is known as the city of Islamic student. Method: analytic descriptive with a cross-sectional approach, 38 respondents based on inclusion and exclusion criteria using purposive sampling. The instrument was a questionnaire with 31 questions, analyzed univariate and bivariate using the chie square. Purpose: know the relationship between the level of knowledge about HIV / AIDS and the use of Care, Support, and Treatment services for x Female Sexual Workers. Result: It is known that x Female Sexual Workers have knowledge in good categories, namely as many as 20 people (52.6 It is known that 26 x Female Sex Workers benefit from CST services (68.4%), it is known that there is a relationship between the level of knowledge and CST services in the city of Tasikmalaya with a p-value = 0.019. Discussion: the results of this study indicate that the respondent's good knowledge will not force himself to continue working as a female sexual worker so that it has a positive impact on him and prevents the spread of new sufferers. It is recommended to create a CST service support program that can increase knowledge and provide motivation to people with HIV / AIDS.